A quality control study on Sanitary Wares Corporation PF 0900 Heron Washbasin - Arsenal, Ray; Cuerda, Kristine Rose; Rigor, May; Sobrevinas, Arlene (College of Engineering, 1997)
This is a quality control study conducted on Sanitary Wares Manufacturing Corporation from September to October 1996. It is an application of the principles learned in I.E. 135, specifically in Industrial Quality Control. The product under study is the PF 0900 Heron Washbasin. The group chose this product because of all the product types the PF 0900 has the lowest "A" percentage. It is a relatively new design and is part of the line of products that Saniwares exports to Australia. Its specifications and quality requirements is based on the Standards Australia (AS 1976-1992), Vitreous China Used in Sanitary Appliances. The PF 0900 is basically made of a special type of clay. It undergoes six major processes and two inspections-mold making, slip preparation, cast making, greenware inspection, glaze preparation, spraying, firing, and glost inspection. After the glost (final) inspection, the products are now classified as either "A", "refire", or "loss" means that the defect of the product is not allowable so the product cannot be sold anymore. "Refire" units has defects that can still be remedied and they will be brought to the Refire Department for further processing. The production yield from April to August 1996 was analyzed and it was found out that the PF 0900 has a high refire percentage. This means that the company was experiencing high additional costs because of further processing. A refire analysis was attained and it was determined that almost 50 percent of refire cases can be attributed to clay cracks. Further more. Clay cracks can be traced to problems in cast making. From the Failure Mode and Effects Analysis conducted at the cast shop, it was known that the critical factors were mostly human and machine errors. The following problems were encountered : inspectors do not apply Australian specifications but instead follow the local standards. Workers are not very attentive to detail and does not strive to produce more A" products because they are paid on a fixed rate basis. Summary of Production Reports are inconclusive, they do not tell you the total "A" and total "loss". Workers lack knowledge of the right procedures. The following are the group's recommendations : use of method sheets and proper training for the workers. Inspectors should be briefed about the correct standards to apply for each product type. Reformat production reports so that the management can keep track of its total losses. Introduce a modified piecework salary plan, wherein the worker's pay is based dependent on the saleable units that he produced.